2023
DOI: 10.1249/mss.0000000000003221
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Mental Fatigue Does Not Impact Neuromuscular Function and Exercise Performance

Abstract: Introduction Recent studies have questioned previous empirical evidence that mental fatigue negatively impacts physical performance. The purpose of this study was to investigate the critical role of individual differences in mental fatigue susceptibility by analyzing the neurophysiological and physical responses to an individualized mental fatigue task. Methods In a preregistered (https://osf.io/xc8nr/), randomized, within-participant design experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…MF can affect the activation of the prefrontal cortex, which is an important component of motor networks and plays a role in inhibitory control and fatigue during exercise. However, previous studies have also reported that corticospinal excitability and neuromuscular parameters may not be significantly affected following MF (Holgado et al, 2023;Morris & Christie, 2020;Pageaux et al, 2015). A recent review suggested that nearly half of studies reported no significant effects of MF on various measures of sports performance (Pageaux & Lepers, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…MF can affect the activation of the prefrontal cortex, which is an important component of motor networks and plays a role in inhibitory control and fatigue during exercise. However, previous studies have also reported that corticospinal excitability and neuromuscular parameters may not be significantly affected following MF (Holgado et al, 2023;Morris & Christie, 2020;Pageaux et al, 2015). A recent review suggested that nearly half of studies reported no significant effects of MF on various measures of sports performance (Pageaux & Lepers, 2018).…”
Section: Discussionmentioning
confidence: 98%